1991
DOI: 10.1143/jjap.30.l798
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting YBa2Cu3O7-δ Particles Prepared from Freeze-Dried Nitrates

Abstract: The differential cross sections for electron transfer in Li + -Na(3s) collisions in the 0.4-14 keV energy range are studied using the impact parameter semiclassical method and a 28-state molecular orbital basis model including a common translational factor. The calculated differential cross section (DCS) for electron transfer to Li(2s) and Li(2p) and the three Stokes parameters of the Li(2p) final state are in excellent agreement with the measured DCS at 1 keV and 3 keV. The energy dependence of the final-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was observed that the homogeneous nitrate powder synthesized by the freeze-drying method could yield good superconducting powders by the rapid calcination method, in which the possible segregation of the constituents during decomposition was avoided [201]. The freeze-drying of carbonate slurry for the synthesis of fine and porous YBCO powder was studied by Tachiwaki et al [202].…”
Section: (E) Freeze-drying Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the homogeneous nitrate powder synthesized by the freeze-drying method could yield good superconducting powders by the rapid calcination method, in which the possible segregation of the constituents during decomposition was avoided [201]. The freeze-drying of carbonate slurry for the synthesis of fine and porous YBCO powder was studied by Tachiwaki et al [202].…”
Section: (E) Freeze-drying Methodsmentioning
confidence: 99%
“…Require proper heating schedule to avoid segregation. [196][197][198][199][200][201][202] Aerosol process Single-step process for homogeneous powder with control shapes and sizes.…”
Section: Solution-drying Processmentioning
confidence: 99%